Expression of Angiogenic Factors in Craniopharyngiomas: Implications for Tumor Recurrence - (:unkn) unknown (OXFORD UNIV PRESS INC, 2010)
BACKGROUND: The primary treatment for craniopharyngiomas is total excision, but recurrence is common. However, current knowledge on the mechanisms of recurrence is limited. OBJECTIVE: We hypothesized that recurrence is linked to the angiogenesis of the tumor. Recurrent and nonrecurrent tumor samples were compared with regard to expression of angiogenesis-related factors and angiogenic capacity in a corneal angiogenesis model. METHODS: Specimens of 4 recurrent and 6 nonrecurrent tumors were selected from 57 patients with adamantinomatous craniopharyngiomas. Sections were immunohistochemically stained with antibodies for vascular endothelial growth factor (VEGF), fibronectin, fibroblast growth factor (FGF)-2, platelet-derived growth factor (PDGF)-A, PDGF-B, platelet-derived growth factor receptor (PDGFR)-alpha, and PDGFR-beta. Expression levels were graded using a 4-point scoring system and were compared. For corneal angiogenesis assay, tissue samples were inoculated in a micropocket created on the rat eye, and microvessels were counted on days 3, 5, 7, and 9 to evaluate angiogenic potential. RESULTS: Expression of PDGFR-a and FGF-2 were significantly higher for recurrent tumors (P = .02 and P = .01). However, recurrent and nonrecurrent tumors did not differ in the expressions of other ligands and receptors (PDGF-A, PDGF-B, and PDGFR-beta). Recurrent tumors displayed a higher angiogenic potential starting from the fifth day of corneal angiogenesis assay. CONCLUSION: These findings suggest a relationship between recurrence of craniopharyngiomas and angiogenesis. New treatment modalities with selective PDGFR-alpha blockers may represent a novel and effective therapeutic option for the treatment of craniopharyngiomas.
Keywords: Craniopharyngioma; Fibroblast growth factor 2; Platelet-derived growth factor; Platelet-derived growth factor receptors; Tumor angiogenic potential; Tumor recurrence; GROWTH-FACTORS; IMATINIB MESYLATE; PDGF; PROLIFERATION; MALFORMATION; MANAGEMENT; MENINGIOMA; CARCINOMA; GLIOMAS; CANCER